Parametric study for devulcanization of waste tire rubber utilizing Deep Eutectic Solvent (DES) - Walvekar, Rashmi; Kunju, Kishen; Saputra, Ricky; Siddiqui, Khalid *; Ramarad, Suganti (2018)
Waste rubber is a polymeric material containing 50% of rubber and is generally referred to as waste tyre rubber. The main purpose of this research is to study ultrasonic devulcanisation of waste rubber utilising deep eutectic solvent (DES) of ZnCl2:Urea by improving process parameters such as sonication time, reaction temperature and rubber: DES mass ratio by effectively cleaving cross-link sulphur bonds. DES was created and prepared by mixing ZnCl2 with urea at 2:7 and 1:4 molar ratios respectively. Physicochemical properties of the prepared DES was measured using DSC, KFT and TGA analysis to find the freezing point, moisture content and degradation temperature, whereby their freezing point below 60°C, moisture content lower than 3.0 wt.% and 200°C degradation temperature average. Rubber to DES mass ratio was varied at 1:20, 1:30 and 1:40 and sonicated for 15 minutes inside ultrasonic water-bath. Samples were placed onto hot plate whereby heating temperature was varied at room temperature, 130°C, 150°C, and 180°C for 15 minutes. Samples were filtered, washed with distilled water and dried in oven for 24 hours. Once dried, samples were taken for analysis using TGA, EDX, FESEM, FTIR and Gel content. Under TGA analysis, most samples have an average degradation temperature of 200°C, hence justifying a successful devulcanisation. EDX analysis shows two occurrences during devulcanisation process which is bond reformation and cleavage. Furthermore, it is determined that heating temperature of 130°C is an important parameter as it is the optimum temperature for ZnCl2:Urea. Under FTIR analysis, it shows that disulphide bond, S-S is the only bond that is being broken while the rest still remains the same. Gel content analysis showed that samples have a lower soluble fraction after devulcanisation process. Finally, FESEM proves that at 130°C and 15 minutes is the optimum temperature and time which is illustrated by the smooth surface at that particular point.